STUDI PERBANDINGAN PELEPASAN DAN STABILITAS FISIK APMS DALAM SISTEM NANOSTRUCTURED LIPID CARRIERS (NLC), SOLID LIPID NANOPARTICLES (SLN), DAN NANOEMULSI (NE) (Lipid Padat Kombinasi Oleum Cacao-Beeswax dan Lipid Cair Minyak Zaitun) - BASTIANA RIZKA RACHMAWATI, 051511133133 (2019)
PMCA is an anti-inflammatory which has low solubility in water so it can affect the drug release rate, the rate of penetration, and its effectiveness. To overcome this problem, there are some drug carrier systems that can be used, namely NLC, SLN, and NE. The difference among these three systems is the composition of the lipid phase. The lipid phase of NE is only consist of liquid lipids, whereas SLN is only consist of solid lipids, and the lipid phase of NLC is a combination of liquid solid lipid. The composition of solid and liquid lipids can affect the characteristics and the drug release rate of the system. The purpose of this study is to compare the drug release rate of APMS from the NLC, SLN, and NE systems and the physical stability of the system with the real time method. Evaluation characteristics include organoleptic, pH, particle size and PI, viscosity, melting point and crystallization index, and entrapment efficiency. The results obtained NE-APMS has the largest drug release rate (0.4690 μg/cm2.minute) which can be influenced by the characteristics of NE-APMS which has a low viscosity and small particle size. The results of the physical stability test (color, odor, and consistency) of the system with real time methods show that NLC-APMS is the most stable system.